Development of Water Management Programme for the Tanjung Karang Rice Irrigation Project Using Geographic Information System (GIS) - Khatun, Abeda (2000)
Water plays an important role in crop production. Good water management can improve the irrigation efficiency and the potential to greatly increase crop production. The water availability is dependent on rainfall and irrigation system characteristics. In contributing to the process of decision making the irrigation personnel needs to understand the rainfall pattern and irrigation water demand of the whole system. The Tanjung Karang Rice Irrigation Project in Northwest Selangor Malaysia was selected for this study and the tertiary canal TASB-4 of Sungui Burung compartment was considered as the main study area. Geographic information system (GIS) is becoming an increasingly powerful tool used in water management system for paddy field irrigation. The Tanjung Karang Rice Irrigation Project and soil maps were digitized by the use of Maplnfo Software. Different types of map features such as scheme, compartments, canals, rivers, roads and soils were digitized and stored into different layers. Relevant physical and management data were collected from various sources and input into a database. The application of the GIS software through the development and presentation of water distribution system using tables, maps and graphs were illustrated. Real and some estimated data, using established technique were input into Maplnfo browser tables for each compartment. Proper water budgeting is a prerequisite condition of any successful irrigation project. In an irrigation project, the amount of water to be applied is an important factor. Irrigation scheduling which anticipates the temporal water need of crops i.e. when to irrigate and how much water to apply is an important management activity affecting the performance of the irrigation project. A water budget for dry and normal year was prepared on the basis of the rainfall availability (1950-1997) in the project area. In off-season the total design water requirement was 1314 mm but the total mean rainfall was 444 mm, and in 1 in 5 dry year was 382 mm. So 870 mm and 932 mm of additional water was required for normal and 1 in 5 dry year respectively. Similarly in the main season, the total design water requirement was 1589 mm but the total mean rainfall was 730 mm and 643 mm in 1 in 5 dry year. So 859 mm and 946 mm of additional water was required for normal and 1 in 5 dry year. A cropping schedule calendar was prepared on weekly interval. And on the basis of the calendar, scheduling browser tables of the eight compartments were developed. The water duty of the project area calculated for the 1 st pre-saturation period was 2.78 l/sec/ha, second pre-saturation period was 1.85 l/sec/ha and normal supply period was 1.17l/sec/ha. On the basis of the water duty the irrigation scheduling was then calculated. Other than downstream areas furthest from the main canal, the soils with high percolation rate also influence the quantity of irrigation water available. On the basis of the particle size analysis of the overall soil series, the Jawa, Sedu, and Brown Clay soil series were found to be potential water stress areas of the Tanjung Karang Rice Irrigation Scheme. The Sekinchan compartment was identified as the best productive compartment. By using GIS to monitor the water management, spatial analysis was carried out easily and effectively for modification or maintenance resulting in better water management. Besides, design of water distribution or timely irrigation could also be done to increase the uniformity, efficiency and adequacy of water delivery systems.